A Comparative Study to Analyze the Influence of Quadriceps Flexibility and Vmo Strengthening Using Lunges with Resistance Band Versus Wall Ball Squats With Combined Exercises on Dynamic Patellofemoral Pain Syndrome in Athletes - Divyansh Pareek; Dr. Hirendra kumar katariya PT; Dr.Jafar khan PT (International Journal of Pharmacy Research & Technology (IJPRT), 2026)
Background: Patellofemoral syndrome (PFS), or alternatively referred to as patellofemoral pain syndrome (PFPS) or “runner knee syndrome is one of the most common causes of anterior knee pain in clinical and sports medicine practice. It is noted by diffuse, ill-localised pain around or behind the patella, which is usually exacerbated by knee loading exercises in flexed position like running, climbing stairs, squatting, and sitting. Clinical tests focus on posture, alignment, bulk of the muscles (e.g., vastus medialis atrophy), local tenderness, range of movement, and strength of the quadriceps and hip muscles. The PFS treatment is largely conservative and aims to manage pain, repair biomechanical dysfunction, and restore function. The first line of treatment consists of activity modification, temporary use of non-steroidal anti-inflammatory drugs (NSAIDs), and modalities such as ice to relieve symptoms during the acute stage. Nevertheless, structured rehabilitation programs are most often associated with long-term improvement. The therapeutic exercise geared toward enhancing strength, flexibility, and neuromuscular control of the knee and hip has always been found to be the most effective. In this study resistance-band lunge training and wall ball squats combined with therapeutic exercises has been introduce to reduce pain and improve function. Objective: The objective of the study is to i) evaluate the effect of resistance-band lunge training, ii) evaluate the effect of wall ball squats combined with therapeutic exercises, iii) compare the outcomes between the two intervention programs to determine which approach is more effective. Methods: 30 athletes diagnosed with the patellofemoral pain syndrome (PFPS) by orthopedic OPD or physiotherapy department were initially assessed for the inclusion or exclusion criteria. Prior to the treatment procedure patient are oriented to the study. Participants are divided into 2 groups and both groups assessed for the pre test parameter. Outcome measure: VAS (Visual Analog Scale), and Kujala Questionnaire Scale is used for measuring pre and post intervention evaluation. Results: The results illustrate that pain reduction and functional improvement do not always follow the same trajectory, and different exercise strategies may target different aspects of patellofemoral pain syndrome. Thera-band lunges proved to be an excellent choice for rapidly reducing pain, while wall ball squats and associated neuromuscular exercises were more effective for developing overall functional capabilities needed for sports and higher-level activities. Although both groups improved, the study’s outcomes suggest that an optimal rehabilitation approach may blend elements from both interventions-using pain-reducing strategies early on and gradually transitioning into functional strengthening and neuromuscular control exercises as pain subsides. Conclusion: The findings of the present investigation clearly demonstrate that both interventions produced substantial improvements in pain and functional outcomes by the end of the intervention period.